Who's buying for travel. (Who's buying series., 2015)
The eleventh edition of Who's Buying for Travel is based on unpublished data collected by the Bureau of Labor Statistics' 2013 Consumer Expenditure Survey-you can't get these data online. It examines how much Americans spend on getting out of town by the demographics that count: age, income, high-income households, household type, race and Hispanic origin, region of residence, and education. To round out the spending picture, it also presents who-are-the-best-customers analyses of the data, showing the demographics of the best and biggest customers at a glance.